LOOKING FOR A RELATIONSHIP BETWEEN METACOGNITIVE AWARENESS AND PROBLEM SOLVING SKILLS IN PHYSICS - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2017)
The purpose of this research was to examine the relationship between students' metacognition awareness and their problem solving skills in physics. Both qualitative and quantitative methods were carried out. The participants were 30 eleventh graders studying in an urban all-boys school. After the participants' metacognitive awareness was determined, they were video recorded by using think-aloud protocol while solving various levels of physics problems. The students' verbalizations of their thinking and their written solutions for the problems were used to code them as experts and novices. More than half of the students were categorized as novice problem solvers. Although no significant relationship was found between metacognition and problem solving, there were some qualitative patterns between the two.
Keywords: Metacognition; problem solving; physics; high school students; LEARNING-DISABILITIES; STUDENTS